HIGHER EDUCATION IN INDIA THROUGH MOOCs AND ONLINE COURSES - Kaicker, Anju; Mathur, Pranav; Jawed, Sumaiya (International Journal of Research -GRANTHAALAYAH, 2022)
Online education has seen a rapid and significant growth in the 21st century. Online courses and MOOCs have had an extremely positive impact on higher education in India. Herein, is an attempt to study the growing sphere of online education in India, with special reference to developments in the past decade. In the study, the authors have examined the role of the public and private sector in the field of education. SWAYAM is an indigenous platform of the Government of India which hosts numerous courses and has attracted learners from all age groups and across different streams. Simultaneous growth of educational start-ups in the last decade has enhanced employment generation as well as opened up new avenues for professional growth. Growing collaborations between educational start-ups and foreign universities is helping in globalization of education. The paper compares private and public online courses and discusses how online education has positively impacted employability across various sectors. The various challenges posed in online education have also been elaborated.